ANALISIS KINERJA ASPAL PEN 60/70 DAN ASPAL POLIMER JAP-57 DALAM CAPURAN ASPAL PORUS - Dea Anggiani; Imam Hagni Puspito; Wita Meutia (Jurnal Infrastruktur, 2018)
Porous asphalt is an asphalt mixture which has a higher porosity value compared to other asphalt mixtures. The function of the high porosity value is to pass the water that goes through the pores of the mixture. This research is done with the aim to analyze 60/70-penetration asphalt performance that modified with low-density polyethylene plastic mix and JAP-57 polymer asphalt in porous asphalt mixture. This research is done by conducting the manufacture of test specimens in accordance with the variation of asphalt content plan among others 4%, 4,5%, 5%, 5,5% ,6% and added 3%, 5%, 7% plastics of total asphalt requirement. The resulting test objects will be subsequently performed Marshall testing to get the parameters of void in mix (VIM), stability, flow and marshall quotient, which will be analyzed according to the Australian Asphalt Pavement Association specification. From the results of the research, obtained the optimum asphalt content (OAC) in each mixture. And from the optimum asphalt content known that the marshall parameter that meets the specification is on JAP-57 porous asphalt mixture with optimum asphalt content of 4,4%. With the value of void in mix (VIM) 18,85%, stability value 539,10 Kg, Flow 2,86 mm and marshall quotient 188,30 Kg/mm.